A grande missão do século XIX e a escrita da história de Ernest Renan (1848-1863) - Rudi, Thiago Augusto Modesto [UNESP] (2014)
This dissertation starts from the following question: what was writing History like in midnineteenth century? In order to add some meaning to it, the writings of the French historian Joseph-Ernest Renan (1823-1892), between the years 1848 and 1863 were considered as its specific object. Through the reading of Renan’s books and articles and the records of the institutions of which the author had been a member, the study aimed to understand the procedures and conceptions that guided his writing of history. This study provided the understanding that, at first, Renan characterized the history as the great mission and work of his century. This mission that defined history as a religion and as a science, simultaneously endeavored to situate the history in a prime location for the significance of science and religions. In dialogue with historians such as Augustin Thierry and Wilhelm von Humboldt and authorized by places such as the Société Asiatique and the Académie des Inscriptions et Belles-Lettres, Renan became one of the missionaries who, for love of truth, interwove the thorough critique of the documents to the intents of Philosophy of History in a self-reflective, verisimilar writing, endower of senses and movements to the past